Bridging the gap: Toward a holistic understanding of shared micromobility fleet development dynamics - Shahnaz N. Fuady; Paul C. Pfaffenbichler; Yusak O. Susilo (Communications in Transportation Research)
Rapid urbanization and shifting demographics worldwide necessitate innovative urban transportation solutions. Shared micromobility systems, such as bicycle- and scooter-sharing programs, have emerged as promising alternatives to traditional urban mobility challenges. This study delves into the complexity of shared micromobility fleet development, focusing on the interplay between fleet size, user demand, regulatory frameworks, economic viability, and public engagement. By employing a system dynamics modeling approach that incorporates causal loop diagrams (CLDs) and stock and flow models (SFMs), we explore various policy scenarios to optimize micromobility management systems. Our findings reveal that financial incentives, such as fee reductions and government subsidies, significantly increase user adoption and profitability, whereas increased operational fees necessitate a delicate balance between cost management and service attractiveness. Sensitivity and uncertainty analyses highlight critical parameters for effective fleet management. This research offers actionable insights for policymakers and operators, promoting sustainable urban transport systems.